A Study of Problem Based Learning and Mathematics Process Skills In Elementary School - Kamid, Kamid; Sabil, Husni; Syafmen, Wardi; Triani, Elza (Jurnal Ilmiah Sekolah Dasar, 2021)
This type of research is experimental quantitative research by comparing 4 classes using the PBL model. The sample in this study was 144 students from SD Negeri 156/I Bulian Baru and SD Negeri 001/I Pasar Muara Tembesi and MIS Darul Aufa and MIS Nurul Jadid. This study uses quantitative data analysis with the help of SPSS statistics 25, to find descriptive statistics and inferential statistics. Important research is carried out as a reference for an educator in understanding the appropriate learning method or model for a lesson to be taught. This study aims to determine the comparison of student process skills and student responses to the PBL learning model in SD/MI, and to determine the relationship between student responses to student responses to the PBL learning model and student process skills. The results of the T test showed that in each school there were differences in process skills and student responses to the PBL learning model. The results of the correlation test in each school showed that the student's response to the student's response to the PBL learning model had an effect on the student's process skills.